2015
DOI: 10.3390/ijms16010924
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism, Apoptosis and Cancer Therapy

Abstract: Lipid metabolism is regulated by multiple signaling pathways, and generates a variety of bioactive lipid molecules. These bioactive lipid molecules known as signaling molecules, such as fatty acid, eicosanoids, diacylglycerol, phosphatidic acid, lysophophatidic acid, ceramide, sphingosine, sphingosine-1-phosphate, phosphatidylinositol-3 phosphate, and cholesterol, are involved in the activation or regulation of different signaling pathways. Lipid metabolism participates in the regulation of many cellular proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
246
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(260 citation statements)
references
References 174 publications
(223 reference statements)
5
246
0
9
Order By: Relevance
“…PEs are generated from the Kennedy pathway and CDP-DAG pathway [31]. It has been demonstrated that PEs were significantly increased in HCC tissue [29,32], which is consistent with our results.…”
Section: Altered Lipid Species Associated With Hccsupporting
confidence: 93%
“…PEs are generated from the Kennedy pathway and CDP-DAG pathway [31]. It has been demonstrated that PEs were significantly increased in HCC tissue [29,32], which is consistent with our results.…”
Section: Altered Lipid Species Associated With Hccsupporting
confidence: 93%
“…Because tumors can recur, however, PDT is combined with other anticancer drugs to improve its therapeutic benefit. Sphingolipids include membrane-bound bioactive lipids that can act as anticancer agents [2]. We and others have shown that stresses, including Pc4-mediated PDT, can perturb the de novo sphingolipid biosynthesis (DNS) pathway, leading to changes in the levels of its intermediates, which are potent regulators of cell death [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidine metabolism, and in general nucleotide metabolism, is widely known to play an important role in cancerous proliferation, as a sufficient pool of nucleotides is necessary for the requisite DNA replication of mitosis during proliferation 38 . Changes were also identified in lipid metabolism pathways; lipid metabolism is known to be implicated in cancer, and lipid signaling mediates many cellular mechanisms, including apoptosis 39 . Changes in lipid pathways could be indicative of some direct effect of menaquinone, an indirect effect mediated by phosphoethanolamine, or an even more indirect effect as the result of induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%